Multilayered electrospun nanofibrous scaffolds for tailored controlled release of embelin. Issue 1 (2nd January 2018) - Cortez Tornello, Pablo R.; Feresin, Gabriela E.; Tapia, Alejandro; Cuadrado, Teresita R.; Abraham, Gustavo A.
ABSTRACT: Polymeric electrospun meshes are highly attractive as versatile platforms for numerous biomedical applications, tissue engineering, biosensors, and controlled release of bioactive agents. Herein, we describe the preparation and characterization of multilayered nanofibrous poly(ε-caprolactone) scaffolds with different embelin content by electrospinning technique. In vitro release in physiological and acidic pH and kinetic analysis were performed. The results show that it is possible to modulate the release profile depending on the number and thickness of layers added to drug-loaded scaffold that acts as an embelin reservoir. Electrospun multilayered scaffolds present characteristics, morphology and release profiles that could be very attractive for use as embelin controlled release systems.